2016
DOI: 10.1007/s00520-016-3532-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of adhesive capsulitis of the shoulder after breast cancer treatment

Abstract: Adhesive capsulitis of the shoulder is a common problem after breast cancer treatment. An age of 50-59 years and mastectomy are major risk factors for adhesive capsulitis, and breast reconstruction additionally increases the risk. Patients with these risk factors require greater attention for early diagnosis and proper treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 26 publications
2
57
0
Order By: Relevance
“…About half of the patients with chronic pain after breast cancer surgery showed neuropathic features such as paresthesia, allodynia, and phantom sensation 7 ; therefore, chronic shoulder pain after breast cancer surgery was assumed as neuropathic pain. However, a recent study showed adhesive capsulitis occurred in about 10% of patients who underwent breast cancer surgery 15 . Although the aforementioned study showed the possibility of structural damage in breast cancer patients with chronic pain, the diagnosis of adhesive capsulitis was based only on medical charts 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About half of the patients with chronic pain after breast cancer surgery showed neuropathic features such as paresthesia, allodynia, and phantom sensation 7 ; therefore, chronic shoulder pain after breast cancer surgery was assumed as neuropathic pain. However, a recent study showed adhesive capsulitis occurred in about 10% of patients who underwent breast cancer surgery 15 . Although the aforementioned study showed the possibility of structural damage in breast cancer patients with chronic pain, the diagnosis of adhesive capsulitis was based only on medical charts 15.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive capsulitis is often known as "frozen shoulder, " because it has the characteristics of progressive pain and limited range of motion 14 . One study revealed that approximately 10% of breast cancer patients suffered from adhesive capsulitis, and a history of mastectomy was a major factor associated with adhesive capsulitis 15 . However, previous study diagnosed adhesive capsulitis only by a medical chart review and did not confirm adhesive capsulitis by imaging analysis 15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the limited motion of the shoulder joint was reported to be impaired in 0.8% to 67% of patients who underwent breast cancer surgery, the incidence of definite FS has been rarely reported. Yang et al reported that cumulative and current FS at 13‐18 months after breast cancer surgery was observed in 10.3% (28 of 271) and 7.7% of patients (21 of 271), respectively. Yang et al reported that the incidence of FS after breast cancer surgery 3.7%, 3.7%, and 1.1% at 3, 6, and 12 months after surgery.…”
Section: Subject Demographics and Characteristicsmentioning
confidence: 99%
“…There has been considerable interest in comparing the contribution of different surgical techniques to the occurrence of FS. In particular, several studies reported that the mastectomy was found to increase the risk of FS, although mastectomy does not directly damage the glenohumeral joint . Pectoralis muscle tightness after a mastectomy is greater when compared with breast‐conserving surgery and these biomechanical changes could cause impingement and stress of the joint capsule, resulting in secondary FS.…”
Section: Subject Demographics and Characteristicsmentioning
confidence: 99%